2018 IEEE International Conference on Cluster Computing (CLUSTER) 2018
DOI: 10.1109/cluster.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Sparse Matrix Classification Based on Deep Learning Techniques

Abstract: In this paper, a new methodology to select the best storage format for sparse matrices based on deep learning techniques is introduced. We focus on the selection of the proper format for the sparse matrixvector multiplication (SpMV), which is one of the most important computational kernels in many scientific and engineering applications. Our approach considers the sparsity pattern of the matrices as an image, using the RGB channels to code several of the matrix properties. As a consequence, we generate image d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The previous method allows to generate easily a binary image dataset that fits a CNN. However, we demonstrated that datasets of that type do not provide satisfactory classification results [3]. We must take into account that scaling down a sparse matrix simplifies the appearance of its sparsity pattern, causing a loss in the information provided to the CNN in the training phase.…”
Section: Classification Methodologymentioning
confidence: 97%
See 4 more Smart Citations
“…The previous method allows to generate easily a binary image dataset that fits a CNN. However, we demonstrated that datasets of that type do not provide satisfactory classification results [3]. We must take into account that scaling down a sparse matrix simplifies the appearance of its sparsity pattern, causing a loss in the information provided to the CNN in the training phase.…”
Section: Classification Methodologymentioning
confidence: 97%
“…This section summarizes the methodology to select the best performing format for a particular sparse matrix with the aim of maximizing its SpMV performance [3]. Figure 2 shows an scheme with the different stages of our approach.…”
Section: Classification Methodologymentioning
confidence: 99%
See 3 more Smart Citations